(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the basic principles of TPR, its role in the learning process and its advantages. It also discusses methods for developing students’ linguistic and communicative skills through physical movements and interactive activities. The effectiveness of TPR is illustrated through practical examples such as role-playing, action-based stories and interactive classroom games. The main advantages of the method are stress-free language learning, increased memory and encouraging active participation.